The poetry of W.B. Yeats: a reader's guide to essential criticism
Auden said to the ghost of Yeats in his famous elegy, when he died 'he became his admirers'. This Guide follows the often heated debates on who Yeats was and what kind of poetry he wrote. Michael Faherty offers selections from the leading voices in these debates, setting them in the context of Irish cultural and political history.